Validation of a questionnaire for orthostatic hypotension for routine clinical use. Issue 7 (14th July 2015) - Frith, James; Newton, Julia L
Abstract : Aim: To validate a new patient‐reported outcome measure for routine clinical use. Methods: A total of 50 older individuals with orthostatic hypotension who attended a falls and syncope clinic completed three questionnaires, the recently developed Orthostatic Hypotension Questionnaire, the existing Orthostatic Grading Scale and the quality of life measure EQ‐5D‐5L. Validity of the Orthostatic Hypotension Questionnaire was tested against the aforementioned questionnaires for symptoms and for quality of life. Comorbidity was quantified using the Charlson Comorbidity Index. Results: The cohort of 50 individuals had a median age of 67 years (interquartile range 26–89 years) with a median Charlson Comorbidity Index of 3 (interquartile range 2–5). The total Orthostatic Hypotension Questionnaire Symptom Assessment score correlated strongly with the Orthostatic Grading Scale (0.616, P  < 0.001) and the Orthostatic Hypotension Questionnaire Daily Activity Scale correlated strongly with daily activity on the EQ‐5D‐5L (0.61, P  < 0.001). Using the Orthostatic Grading Scale, individuals' symptoms were categorized as mild, moderate or severe, the Orthostatic Hypotension Questionnaire scores were significantly different between these groups ( P  < 0.001). Internal consistency was high (Cronbach's apha 0.882), and ceiling or floor effects did not limit the total scores. Conclusion: The Orthostatic Hypotension Questionnaire is a valid patient report tool to quantify the symptom burden of people with orthostatic hypotension. Because the symptoms associated with orthostatic hypotension are frequently non‐specific, it will be a clinically useful tool to measure and quantify symptom load in people with orthostatic hypotension.Geriatr Gerontol Int 2016; 16: 785–790.